N,Ndimethylformamide.diiodine complex (DMF.I2) as an innovative efficient green catalyst in the synthesis of thiosemicarbazones by condensation of ketones with thiosemicarbazides - Kasséhin, Urbain C.; Gbaguidi, Fernand A.; McCurdy, Christopher R.; Poupaert, Jacques H. (My University, 2015)
In a drug discovery program aimed at finding new anti-trypanosomal drugs, we developed the N, Ndimethylformamide.diiodine complex (DMF.I2) as an innovative and efficient green catalyst for the condensation reaction of aldehydes/ketones with arylthiosemicarbazides. The design of this catalyst was rationalized on the basis of a mechanistic proposal which establishes the existence of a catalytic loop regenerating I2 at the end of the catalytic process. In general, yields were fair to good at extremely low end catalyst concentration. DMF.I2 is the first catalyst that allows for high yield in the condensation of aldehydes/ketones with arylthiosemicarbazide at sub-micromolar concentration.
Keywords: Green chemistry; Dimethylformamide-diiodine complex (DMF.I2); Trypanosomal infections; arylthiosemicarbazides; Thiosemicarbazones